A new leptoceratopsid (Ornithischia: Ceratopsia) from the Upper Cretaceous of Shandong, China and its implications for neoceratopsian evolution. - Xing Xu (Public Library of Science (PLoS), 2010)
Background The ceratopsians represent one of the last dinosaurian radiations. Traditionally the only universally accepted speciose clade within the group was the Ceratopsidae. However, recent discoveries and phylogenetic analyses have led to the recognition of a new speciose clade, the Leptoceratopsidae, which is predominantly known from the Upper Cretaceous of North America. Methodology/principal findings Here we report a new leptoceratopsid taxon, Zhuchengceratops inexpectus gen. et sp. nov., based on a partial, articulated skeleton recovered from the Upper Cretaceous Wangshi Group of Zhucheng, Shandong Province, China. Although Zhuchengceratops is significantly different from other known leptoceratopsids, it is recovered as a derived member of the group by our phylogenetic analysis. Furthermore, Zhuchengceratops exhibits several features previously unknown in leptoceratopsids but seen in ceratopsids and their close relatives, suggesting that the distribution of morphological features within ceratopsians is more complex than previously realized. Conclusion/significance The discovery of Zhuchengceratops increases both the taxonomic diversity and the morphological disparity of the Leptoceratopsidae, providing further support for the hypothesis that this clade represents a successful radiation of horned dinosaurs in parallel with the Ceratopsidae in the Late Cretaceous. This documents a surprising case of the coexistence and radiation of two closely-related lineages with contrasting suites of jaw and dental features that probably reflect adaptation to different food resources.